Mechanism of Ru(VI) Catalysis in Potassium Bromate oxidation of Cyclopentanol in Alkaline Media - Singh, Darshana; Bhusan Singh, Shashi; Prakash sahay, Ved; Prasad, Manju; Prasad, Janak (Asian Journal of Chemistry, 2010)
The kinetic data obtained in Ru(VI) catalysed oxidation of cyclopentanol by alkaline solution of potassium bromate in the presence of mercuric acetate as bromide ions scavenger have been reported. First order kinetics with respect to each of bromate ion, Ru(VI) and cyclopentanol was observed. Zero order dependence on [OH–] and negligible effect of variation of ionic strength of the medium were observed while successive addition of mercuric acetate shows zero effect on the reaction velocity. Mechanistic aspects are discussed.